STRATEGI KOMUNIKASI DINAS KEPEMUDAAN OLAHRAGA DAN PARIWISATA DALAM MENINGKATKAN KUNJUNGAN DESA WISATA RANTAU LANGSAT DI KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Putri Anggraini; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indragiri Hulu Regency is one of the regencies that has natural potential that can be used as a leading tourism destination. Rantau Langsat Village is one of the areas in Indragiri Hulu Regency which has various forms of tourism in it. This tourist destination is program as one of the ecotourism in Riau Province. Of course, in carrying out this discourse, it is inseparable from the communication strategy carried out by the Youth, Sports and Tourism Office. The purpose of this study was to determine the strategy for selecting communicators, message composition, media selection and target audience determination.        The method used is a qualitative research method. The research was conducted at the Department of Youth, Sports and Tourism, Indragiri Hulu Regency. Data collection techniques with interviews, observation and documentation. There were 6 informants, namely 2 from the Youth, Sports and Tourism Office of Indragiri Hulu Regency, 2 from the management of the Rantau Salo tourism awareness group and 2 visitors. The data validity technique uses triangulation and participation expansion.        The results of this study indicate that the communication strategy carried out by the Youth, Sports and Tourism Office of Indragiri Hulu Regency in attracting tourist visits to Rantau Langsat tourist destinations is to determine that communicators have credibility and broad knowledge about Rantau Langsat tourist destinations. informative and persuasive while in the media selection strategy, the Youth Sports and Tourism Office uses social media Instagram and Facebook and the output media of billboards and banners, then the strategy in determining targets or audiences, the Youth Sports and Tourism Office does not determine the criteria because Rantau Langsat Tourism can be visited both young and old.  Keyword : Communication Strategic, Communicator, Message, Media, Target Audience